Deconstructing the University: An Analysis with a Gender Approach from Socioformation - Freire Muñoz, Irina (2023)
The university is the ideal space to generate a transformation in the socio-cultural patterns of perpetuation of gender differences that promote the denaturalization of violence and discrimination. This essay aims to argue, with a gender perspective, how historically and culturally patriarchal patterns have been built from coloniality in the acquisition of knowledge; in addition, the essay poses the need to move from the theoretical component to an integrated action through the educational model of socio-training to propose a mainstreaming of the gender approach in the substantive functions, teaching, social engagement and research, and above all, in the same way of doing, thinking and feeling the university.